Perlindungan Hukum Hak Atas Kekayaan Intelektual (HAKI) Terhadap Hak Cipta Karya Seni Reog Ponorogo - Geofani, Geofani Lingga Meryadinata (Universitas Kapuas, 2024)
Reog Ponorogo art is protected by the Copyright Law as a form of creation. Efforts to increase public awareness and understanding, especially Reog Ponorogo artists, regarding copyright are still low. It is necessary to implement the Copyright Law appropriately and based on legal awareness to achieve social welfare.